Respuesta :
(-5.12) -(-4.7)+ (7.021)
= -5.12 +4.7 +7.021
= (-5.12 +4.7) +7.021
= -0.42 +7.021
= 6.601.
The final answer is 6.601.
Hope this helps~
= -5.12 +4.7 +7.021
= (-5.12 +4.7) +7.021
= -0.42 +7.021
= 6.601.
The final answer is 6.601.
Hope this helps~
Answer:
(-5.12) - (-4.7) + (7.021) = 6.601
Step-by-step explanation:
Given : expression (-5.12) - (-4.7) + (7.021)
We have to simplify the given expression.
Consider the given expression (-5.12) - (-4.7) + (7.021)
Apply plus - minus rule, [tex]\left(a\right)=a,\:-\left(-a\right)=a[/tex]
we have,
= - 5.12 + 4.7 + 7.021
Adding terms, we have,
= -5.12 + 11.721
Simplify , we get,
= 6.601
Thus, (-5.12) - (-4.7) + (7.021) = 6.601